2018
DOI: 10.1111/prd.12211
|View full text |Cite
|
Sign up to set email alerts
|

Implant placement in the esthetic area: criteria for positioning single and multiple implants

Abstract: Patient expectations from implant treatment have changed over the years and esthetics plays an important role in defining what is now called success of rehabilitation. Of the many factors that influence the outcome of the rehabilitation, the two main ones are the bone and soft-tissue deficiencies at the intended implant site. Many surgical approaches are described in terms of timing of implant placement and management of regenerative procedures. The aim of this article is to discuss the different implant place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 54 publications
(68 reference statements)
1
77
0
18
Order By: Relevance
“…At the same time, Cocchetto and Canullo presented similar outcomes using a hybrid abutment with buccal conical anatomy and palatal margin line. Recently published systematic review confirmed the positive outcomes of conical abutment geometry in terms of soft tissue behavior …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…At the same time, Cocchetto and Canullo presented similar outcomes using a hybrid abutment with buccal conical anatomy and palatal margin line. Recently published systematic review confirmed the positive outcomes of conical abutment geometry in terms of soft tissue behavior …”
Section: Introductionmentioning
confidence: 75%
“…Recently published systematic review confirmed the positive outcomes of conical abutment geometry in terms of soft tissue behavior. 21 The disturbance of the peri-implant mucosal barrier by repeated connection/disconnection of the implant abutment has also been suggested as a factor that may be relevant for early crestal bone stability. 22 Outcomes are controversial, with some studies reporting significant differences between groups subjected to dis/reconnection or not, 23 and others showing no differences.…”
mentioning
confidence: 99%
“…Considering the prosthetic planning, even if the implant had been adequately placed in the apicocoronal and buccopalatal direction, the prosthetic resolution for the implant in the site of tooth 12 would be a distal cantilever of tooth 13. This is a controversial option from a mechanical and biological point of view [ 18 ]. Another option could have been a fixed partial denture using the implant abutment in the site of tooth 12 and a tooth abutment on tooth 14, which was also not considered as the first choice [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…, Testori et al . ). In cases where the affected tooth has no signs of periapical pathosis and the buccal cortical plate is intact, and is an adequate thickness of keratinized tissue, it may be appropriate to consider extraction and immediate implant placement (Kan et al .…”
Section: Extractionmentioning
confidence: 97%